Colégio Sagrado Coração de Jesus, Bento Gonçalves/RS (1956-1972) : processo identitário e cultura escolar compondo uma história - Poletto, Julia Tomedi (My University, 2015)
This dissertation investigates the Colégio Sagrado Coração de Jesus‟s historical process, in Bento Gonçalves - RS. The educational institution researched is part of the Instituto das Apóstolas do Sagrado Coração de Jesus, of Italian origin. The study had the time frame of the year 1956, the date of establishment of the college in the city, until 1972 due to the implementation of LDB 5.692/71 and the consequent changes in the educational process of the college. The narrative produced aimed to construct the identity process and school culture that composed this educational institution in the period surveyed. Written documents (book tumble of Paróquia Cristo Rei, books of minutes and books of final exams of the school), photographs and oral histories of eight subjects linked to the school (two former students, two former teachers, two sisters of the congregation and two residents of the Cidade Alta, the region in which the school was formed) were the main sources of information. Through these sources and the analysis produced from aspects of cultural history, it was possible to identify interesting moves and breaks about the identity process of the college, as the marks of catholic education and ethnicity in the hidden curriculum of the school, and it‟s own congregation, like the participation in the administration of a hospital in the city. The school architecture and some school practices were investigated in the school culture bias and showed particular ways of acting, of being, of living together, of teaching and of learning the subjects in the school. Regarding the school architecture, the analysis was based on the change of the school building throughout the investigated period, pointing out the constructed and experienced representations by the school subjects in these two buildings in which the educational institution worked. The discipline represented as something positive by former students and former teachers, the blended teaching (or co-education) as a facility for locals and "opposite" in certain behaviors presented in the premises of the school, as well as the teaching period were the school practices analyzed, which pointed to the modes of action of individuals in a particular time and space.
A presente dissertação buscou investigar o processo histórico do Colégio Sagrado Coração de Jesus, localizado em Bento Gonçalves – RS. A instituição educativa pesquisada faz parte do Instituto das Apóstolas do Sagrado Coração de Jesus, de origem italiana. O estudo teve como recorte temporal o ano de 1956, data da criação do colégio no município, até 1972, em virtude da implementação da LDB nº 5.692/71 e das consequentes mudanças no processo educativo do colégio. A narrativa produzida teve como objetivo construir o processo identitário e a cultura escolar que compôs esta instituição educativa no período pesquisado. Documentos escritos (livro de tombo da Paróquia Cristo Rei, livros de atas e livros de exames finais do colégio), fotografias e a história oral de oito sujeitos vinculados ao colégio (dois ex-alunos, duas ex- professoras, duas irmãs da congregação e dois moradores da Cidade Alta, região em que a escola se constituiu) foram as principais fontes de informação. Por meio dessas fontes e da análise produzida a partir de aspectos da história cultural, foi possível identificar interessantes movimentos e rupturas do processo identitário do colégio, como as marcas da educação católica e a etnicidade no currículo oculto da escola, e da própria congregação, a exemplo da participação na administração de um hospital do município. A arquitetura escolar e algumas práticas escolares foram investigadas no viés da cultura escolar e apresentaram modos peculiares de agir, de ser, de (con)viver, de ensinar e de aprender dos sujeitos no interior da escola. Em relação à arquitetura escolar, a análise foi pautada na mudança de prédio da escola no período investigado, sinalizando as representações construídas e vivenciadas pelos sujeitos escolares nessas duas edificações em que a instituição educativa funcionou. A disciplina representada como algo positivo pelos ex-alunos e ex-professores, o ensino misto (ou a co-educação) como facilidade para os moradores e “divergente” em algumas condutas presentes no interior da escola, assim como o ensino do período foram as práticas escolares analisadas, as quais apontaram para os modos de agir dos sujeitos, em determinado tempo e espaço.
Keywords: Educação - História - Bento Gonçalves (RS); Prática de ensino; Edifícios escolares; Education - History - Bento Gonçalves (Brazil); Student teaching; School buildings